KEPEMIMPINAN MGR. I. SUHARYO DI KEUSKUPAN AGUNG SEMARANG PERIODE 1997-2009 DALAM TERANG KEPEMIMPINAN ANTHONY DSOUZA - Gunawan, Yohanes (P3TK, Sanata Dharma University, 2013)
By the end of twentieth century, leadership crisis occured in various sectors of life and institutions. In this situation, Christian Leadership associated identically with the leadership model of Jesus Christ is offered to the society. Anthony DSouza formulated the Leadership of Jesus with 3-S formula, namely: Servant, Steward, and Shepherd. The true leadership basically conceived three traits, namely: ennoble, ennable, and empower. This research aims to explore the leadership of Mgr. Ignatius Suharyo in the Archdiocese of Semarang during 1997-2009. He led people of God in the Archdiocese of Semarang during the transition period from the XX century to XXI century. In the transition, two main challenges emerged in the life of society and church, namely: massive stream of globalization and danger of nations disintegration. Mgr. Suharyo wrote 27 letters of shepherd to provide guidance for the people of God. Through these letters, Mgr. Suharyo proposed the idea of Gereja Sebagai Peristiwa (Church as a Happening). This idea reflected his vision of leadership and his ecclesiological perspective to determine the Churchs face. Referring to Anthony DSouzas view of leadership, this research found that Mgr. Suharyo experienced himselfas a leader serving humbly, a steward bearing historical responsibility, and a shepherd having discipline yet gentle nature (fortiter sed suaviter). He also committed his leadership through some ways, namely: giving meaning and inspiring through key words, shifting mindset intelligently, and developing communal sharing (duduk bersama) culture. This leadership model was reflected in his motto: Serviens Domino Cum Omni Humilitate (Acts 20:19). This motto was then realized in his work as the Archbishop of Semarang through words and actions.